A 237-year coral record of Sr/Ca ratios and oxygen isotopes collected from Bicol, the Philippines - Mayuri Inoue; Ayaka Fukushima; Mutsumi Chihara; Ai Genda; Minoru Ikehara; Takashi Okai; Hodaka Kawahata; Fernando Siringan; Atsushi Suzuki (PANGAEA, 2023)
We reconstructed a 237-year record of SST and salinity using a coral core collected at Bicol, southern Luzon, Philippines, which is at the northern edge of the western Pacific warm pool. A 2.5-m-long core (SWGM03–01) was collected from a Porites sp. colony at 6 m below mean sea level on 16 March 2002. Temporal resolution of the Sr/Ca analyses for the most recent 46 years of the record was approximately monthly, whereas for the rest of about 190 years, the resolution was mostly bimonthly. The temporal resolution of the d18O analyses was bimonthly throughout most of the core.